Ease on the cannons, tighten on the trumpets: Geopolitical risk and the transmission of monetary policy shocks - Jochen Güntner; Johannes Henßler (Johannes Kepler University of Linz, Department of Economics, 2021)
Recent advances in the use of high-frequency external instruments to separate the signaling channel of monetary policy from exogenous interest rate changes have solved a number of puzzling responses to supposedly contractionary monetary policy shocks. We show that their effects on U.S. banks' balance sheets, asset markets, and economic activity hinge on the level of geopolitical risk at the time of the FOMC announcement. The S&P500 falls and credit spreads rise by more, while bank balance sheets contract, if geopolitical risk is above its sample median in the quarter or month of the shock. The state-dependent effects are due to a tightening of credit- and risk-related national financial conditions and imply that, while preparing its monetary policy decisions, the Board of Governors should also keep track of the geopolitical environment.
Keywords: E43; E44; E51; E52; 330; C&I loans; Geopolitical risk; Monetary policy; State-dependent effects